Low-dose daylight exposure induces nitric oxide release and maintains cell viability in vitro - Gareth Hazell; Marina Khazova; Paul O’Mahoney (Scientific Reports, 2023)
Abstract Any potential positive effects conferred via sunlight exposure have to be carefully balanced against carcinogenic effects. Here we provide evidence UK sunlight exposure upregulates the cardio protectant nitric oxide (NO) within in vitro skin cell lines with negligible increases in DNA damage and cell death at 1 SED, when compared against unexposed samples. The whole of the ultraviolet A (UV-A) spectrum appears to be responsible for NO release, with efficiency higher at exposures closer to shorter UV-A wavelengths and decreasing with wavelength increases. These results support further in vivo work, which could be of benefit for demographics such as the elderly (that exhibit a natural decline in NO bioavailability).